Effect of feed additive „Poultry Conditioning WS” on the reproductive parameters of breeder geese - Tóth, Péter; Szabó, Csaba; Kerti, Annamária; Hutás, István; Treuer, Ákos; Janbaz, Janan (Animal welfare, Ethology and Housing Systems (AWETH), 2014)
Feed additive “Poultry Conditioning WS” containing trace minerals, essential vitamins and amino-acids was tested for efficiency on the reproductive parameters in two commercial goose flocks kept in semi-extensive and intensive system, respectively. In both system two-two goose flocks were involved in the experiment. The number of treated and control flocks agreed in the semi-extensive system (1500 layers and 500 ganders) and it was similar in the intensive system (476 geese and 182 ganders, 502 layers and 198 genders, respectively). The treated flocks were given the preparation in a dose of 0.1 g/kg live weight in the drinking water at 10 day intervals. In the semi-extensive system the treatment started 10 days before the expectable onset of egg laying, and in the intensive system it began on 10th June. In the semi-extensive system, the treated flock laid 9 eggs more and had 8% higher laying intensity compared to the controls’, but comparable figures were obtained in the two flocks for egg fertility (93.0%-93.5%), hatchability (89%-89%) and the hatch rates were identical (72%-72%). In the intensive system the treated flock laid only one egg more per goose than the control (41 - 40 eggs) but their eggs had slightly higher fertility (87% vs. 82%) and hatching rate (59% vs. 56%).
Keywords: goose; reproduction; feed additive